Analisis Pengaruh Penjualan dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Dwi Ermayanti Susilo; Cindy Leo Rensha (Forum Kerjasama Pendidikan Tinggi, 2023)
The reason for this exploration is to find out what deals and records receivable turnover mean for benefit in assembling organizations that are recorded on the Indonesia Stock Trade from 2017 to 2021. With deals and records receivable turnover filling in as the free factors and productivity as proxied by Net revenue filling in as the reliant variable, this study utilizes a quantitative exploration approach. The data wellsprings of this assessment are discretionary and fundamental data. This study utilized a purposive examining system to choose 27 assembling organizations and 135 information tests from among the organizations that were recorded on the Indonesia Stock Trade somewhere in the range of 2017 and 2019. Numerous direct relapse was the method of information examination used in this study. The results showed that somewhat bargains on a very basic level influence efficiency and records receivable turnover moreover through and through influence benefit. Benefit is influenced at the same time by deals and records receivable turnover.”